Thrombin as Key Mediator of Seizure Development Following Traumatic Brain Injury - Ben Shimon, Marina; Shavit-Stein, Efrat; Altman, Keren; Pick, Chaim G.; Maggio, Nicola (Frontiers in Pharmacology, 2020)
Traumatic brain injury (TBI) commonly leads to development of seizures, accounting for approximately 20% of newly diagnosed epilepsy. Despite the high clinical significance, the mechanisms underlying the development of post traumatic seizures (PTS) remain unclear, compromising appropriate management of these patients. Accumulating evidence suggest that thrombin, the main serine protease of the coagulation cascade, is involved in PTS genesis by mediating inflammation and hyperexcitability following blood brain barrier breakdown. In order to further understand the participation of thrombin in PTS, we generated a combined mild TBI (mTBI) and epilepsy mice model, by injecting pilocarpine to mice previously submitted to head injury. Interestingly, mTBI was able to reduce the threshold of seizure onset as well as increase the death rate in the pilocarpine treated animals. In turn, pilocarpine worsened spatial orientation of mTBI treated mice. Finally, thrombin activity as well as the expression of IL1-β and TNF-α were significantly increased in the mTBI-pilocarpine treated animals. In conclusion, these observations indicate a synergism between thrombin and mTBI in lowering seizure threshold and possibly aggravating inflammation. We believe that these results will improve the understanding of PTS pathophysiology and contribute to the development of more targeted therapies in the future.